Influence of geometrical features of electrospun nylon 6, 6 interleave on the CFRP laminates mechanical properties. Issue 1 (27th August 2013) - Palazzetti, Roberto; Yan, Xiu; Zucchelli, Andrea
<x xml:space="preserve">Abstract</x> Twenty plies, woven carbon fiber/epoxy matrix, virgin, and Nylon 6, 6 electrospun nanofiber interleaved composite laminate beams are tested under Modes I and II fracture mechanic to assess the effect of nanointerleave on the global behavior of the laminate. Aim of the work is to study the effect of geometrical features of the nanoreinforce on the mechanical response of a laminate subjected to fracture mechanic loads. Nanofiber orientation, nanolayer thickness, and nanofiber diameter have been considered. From the experiments, mechanical parameters have been extracted and used to compare the configurations. The work highlights the importance of an accurate choice of the nanointerleave and showed that thick interleaves may weaken the interface if a high number of voids is left after the curing process, the smaller is the fiber diameter the higher is the energy absorbing capability of the specimens, and that fiber orientation has different effect depending on the loading mode. POLYM. COMPOS., 35:137–150, 2014. © 2013 Society of Plastics Engineers